2020
DOI: 10.1002/cjp2.169
|View full text |Cite
|
Sign up to set email alerts
|

Significance of tumour regression in lymph node metastases of gastric and gastro‐oesophageal junction adenocarcinomas

Abstract: The presence of lymph node (LN) metastases is one of the most important negative prognostic factors in upper gastrointestinal carcinomas. Tumour regression similar to that in primary tumours can be observed in LN metastases after neoadjuvant therapy. We evaluated the prognostic impact of histological regression in LNs in 480 adenocarcinomas of the stomach and gastro-oesophageal junction after neoadjuvant chemotherapy. Regressive changes in LNs (nodular and/or hyaline fibrosis, sheets of foamy histiocytes or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
3
18
1
8
Order By: Relevance
“…We therefore decided to apply this system on the esophageal adenocarcinoma cohort, also allowing a direct comparison to the cohort of gastric carcinomas reported previously. The frequency of regressive changes of about 30% in LN metastases of a patient in our study is comparable to other studies, both for esophageal and gastric cancer [13,23,29,36]. One study by Zhu et al [37], however, reported a probability of occurrence of about 64%, which is as twice as much compared to other studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We therefore decided to apply this system on the esophageal adenocarcinoma cohort, also allowing a direct comparison to the cohort of gastric carcinomas reported previously. The frequency of regressive changes of about 30% in LN metastases of a patient in our study is comparable to other studies, both for esophageal and gastric cancer [13,23,29,36]. One study by Zhu et al [37], however, reported a probability of occurrence of about 64%, which is as twice as much compared to other studies.…”
Section: Discussionsupporting
confidence: 87%
“…Even in patients who have not received chemoradiotherapy, fibrosis can occur in the sense of a body's own defensive reaction to tumor cells. However, it has been demonstrated before that the interobserver agreement for the determination of regressive changes in LNM is within substantial levels [13,29].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Unnecessary reporting of nodal regression grade due to the higher prognostic value of LN's residual tumour assessment in predicting the prognosis after NAC was highlighted in a study from the East [108]. Despite usage of similar classification of regressive changes, this result stays in contradiction with European findings [110]. Both, nodal response and the quality of that response correlates with long-term survival.…”
Section: Nodal Regression Gradementioning
confidence: 99%